Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2018)
A dataset containing 166974 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is Human Observation", "Year 1950-2018", "Geometry POLYGON((31.9043 32.9414,49.76368 59.58984,34.43555 80.12109,10.10742 83.00391,-28.56445 68.3789,-37.35351 41.44922,-16.75195 24.57421,13.3418 33.92578,31.9043 32.9414))", "TaxonKey is Vaccinium myrtillus L." ] } The dataset includes 166974 records from 226 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0030228-180508205500799/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences